Detection of Extended-Spectrum Beta-Lactamase (ESBL)-Producing Enterobacteriaceae from Diseased Broiler Chickens in Lusaka District, Zambia - Chikwanda Chileshe; Misheck Shawa; Nelson Phiri; Joseph Ndebe; Cynthia Sipho Khumalo; Chie Nakajima; Masahiro Kajihara; Hideaki Higashi; Hirofumi Sawa; Yasuhiko Suzuki; Walter Muleya; Bernard Mudenda Hang'ombe (MDPI AG, 2024)
Poultry products in Zambia form an integral part of the human diet in many households, as they are cheap and easy to produce. The burden of poultry diseases has, however, remained a major challenge. Growing consumer demand for poultry products in Zambia has resulted in non-prudent antimicrobial use on farms, intending to prevent and treat poultry diseases for growth optimisation and maximising profits. This cross-sectional study aimed to identify the different types of bacteria causing diseases in chickens in Lusaka and to detect the extended-spectrum lactamase (ESBL)-encoding genes. We collected 215 samples from 91 diseased chickens at three post-mortem facilities and screened them for Gram-negative bacteria. Of these samples, 103 tested positive for various clinically relevant Enterobacteriaceae, including Enterobacter (43/103, 41.7%), Escherichia coli (20/103, 19.4%), Salmonella (10/103, 9.7%), and Shigella (8/103, 7.8%). Other isolated bacteria included Yersinia, Morganella, Proteus, and Klebsiella, which accounted for 21.4%. E. coli, Enterobacter, Salmonella, and Shigella were subjected to antimicrobial susceptibility testing. The results revealed that E. coli, Enterobacter, and Shigella were highly resistant to tetracycline, ampicillin, amoxicillin, and trimethoprim-sulfamethoxazole, while Salmonella showed complete susceptibility to all tested antibiotics. The observed resistance patterns correlated with antimicrobial usage estimated from sales data from a large-scale wholesale and retail company. Six (6/14, 42.9%) E. coli isolates tested positive for blaCTX-M, whilst eight (8/14, 57.1%) Enterobacter samples tested positive for blaTEM. Interestingly, four (4/6, 66.7%) of the E. coli isolates carrying blaCTX-M-positive strains were also positive for blaTEM. Sanger sequencing of the PCR products revealed that five (5/6, 83.3%) of the abovementioned isolates possessed the blaCTX-M-15 allele. The results suggest the presence of potentially pathogenic ESBL-producing Enterobacteriaceae in poultry, threatening public health.